2013
DOI: 10.5897/ajb2013.12900
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effect of rice milling waste and supplementary enzyme on performance of broiler chicks

Abstract: A four-week study was conducted to determine the effects of feeding rice milling waste (RMW) and supplementary enzyme (Roxazyme G2 ®) on the performance of broiler chicks. One hundred and twenty (120) 7-day old broiler chicks of Anak strain were randomly divided into eight groups of 15 birds each. The groups were randomly assigned to 8 isocaloric (2.85 Mcal of ME/kg) and isonitrogenous (22.00% crude protein) diets in a 4 × 2 factorial arrangement involving a control (0%), three levels (10, 15 and 20%) of RMW a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Fang et al (2012) elaborated the anti-inflammatory and therapeutic results of acid hydrolysed feurloylated oligosacchrides (FO) from rice bran at dose rate of 0.1-100 µg/mL through increased TNF-a, IL-1b, IL-6 and PGE2 production in RAW264.7 macrophages. Ani et al (2013) concluded that feeding rice milling waste (RMW) improved growth rate through increased feed intake in broiler chicks. Rice is also known as an important immunostimulant and therapeutic agent against avian coccidiosis.…”
Section: Immune Response Modulators Immunostimulatory and Therapeutic Potential Of Rice Branmentioning
confidence: 99%
See 1 more Smart Citation
“…Fang et al (2012) elaborated the anti-inflammatory and therapeutic results of acid hydrolysed feurloylated oligosacchrides (FO) from rice bran at dose rate of 0.1-100 µg/mL through increased TNF-a, IL-1b, IL-6 and PGE2 production in RAW264.7 macrophages. Ani et al (2013) concluded that feeding rice milling waste (RMW) improved growth rate through increased feed intake in broiler chicks. Rice is also known as an important immunostimulant and therapeutic agent against avian coccidiosis.…”
Section: Immune Response Modulators Immunostimulatory and Therapeutic Potential Of Rice Branmentioning
confidence: 99%
“…It was also concluded that rice bran derived arabinoxylans have a potent chemotherapeutic effect against metastatic breast cancer. Ani et al (2013) conducted a study to evaluate comparative effects of feeding rice milling waste (RMW) and Roxazyme G2® enzyme on the performance of broiler chicks. Enzyme supplementation significantly reduced feed intake and improved the performance of birds in terms of average daily weight gain, protein efficiency ratio and feed cost.…”
Section: Immune Response Modulators Immunostimulatory and Therapeutic Potential Of Rice Branmentioning
confidence: 99%
“…It has been estimated that 70-80% of poultry production inputs is been attributed to feed cost, hence making it imperative that good quality feed be available at reasonable price to make poultry production more profitable [4]. For this to happen, there is need to explore the use of alternative and non-conventional feed ingredients that are cheaper and locally available [5]. One of such alternative feed ingredients is rice offal.…”
Section: Introductionmentioning
confidence: 99%
“…Melemahnya efisiensi pakan yang disertai dengan menurunnya pertumbuhan menggambarkan bahwa tidak hanya kandungan serat (insoluble NSP) yang menjadi faktor pembatas penggunaan rice bran dalam ransum broiler pada penelitian ini. Beberapa faktor anti nutrisi lain yang pada umumnya terdapat pada rice bran diantaranya: ketengikan oksidatif dan hidrolitik, kandungan asam fitat dan enzim inhibitor (Gallinger et al, 2004;Ani et al, 2013).…”
unclassified